Degradation of Toxic Dye Using Phytomediated Copper Nanoparticles and Its Free-Radical Scavenging Potential and Antimicrobial Activity against Environmental Pathogens - S. Rajeshkumar; M. Vanaja; Arunachalam Kalirajan (Bioinorganic Chemistry and Applications)
The present investigation deals with the green synthesis of copper nanoparticles in an ecofriendly manner using leaf extract of Andrographis paniculata. Green-synthesized copper nanoparticles were studied for their antibacterial, antioxidant, and catalytic activity. The leaves were powdered and extracted with water and added to copper sulphate solution. The reduction of copper ions to nanoparticles was preliminarily identified by the color change of the reaction mixture. The synthesized nanoparticle was characterized by using a UV-Vis Spectrophotometer at a different wavelength with different time intervals. Functional groups available on the surface of the nanoparticle were identified by Fourier transform infrared spectroscopy (FTIR). Surface roughness was characterized by atomic force microscopy (AFM). X-ray diffraction (XRD) analysis showed six distinct intense peaks indicating the crystalline nature of synthesized copper nanoparticles (CuNPs). A scanning electron microscope (SEM) demonstrated polydispersed nanoparticles formed in the reaction process. The antibacterial activity of the nanoparticles was evaluated by an agar well diffusion assay against pathogenic bacteria. The antioxidant activity showed the excellent reduction of DPPH free radicals by nanoparticles. These results confirmed that copper nanoparticles serve as an alternative therapeutic agent over conventional drugs. Moreover, copper nanoparticles were also used to study the effect on the dye degradation process of methyl red and eosin dyes. Copper nanoparticles effectively remove the dyes with high efficiency up to 92% and 95% of methyl red and eosin dye, respectively.